Cataloging minerals, part 2: Re-imagining the catalog as a first step toward confronting extractionist legacies - Carrie Robbins; Selby Hearth (Museum & Society)
Minerals are uniquely tied to colonialism, labor, and environment; however, those relationships are historically not included in mineral catalogs – an omission that limits curators ability to respond to mineral histories. This essay re-imagines mineral cataloging practices that could provide space for recontextualization efforts: restoring historical, cultural, and environmental context to minerals whose extractions systematically stripped away those relationships. We examine the roles of citations, linked data, provenience and provenance, non-standardized and 'unapproved' nomenclatures, positionality and collaboration, and the significant roles of labeling archival silences. We also examine the significant risks and practical limitations that arise in attempting to turn this colonial tool against itself.